kualitas produk pada UMKM family cattering - Rina Erlita; Awa Awa (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
Micro, Small and Medium Enterprises (MSMEs) in the culinary industry must maintain product quality, which is influenced by food innovation in addition to taste and appearance. Product quality is an important factor in maintaining business competitiveness amidst increasingly tight culinary business competition. However, in catering MSMEs, the implementation of product quality based on indicators of presentation, taste and innovative food is still inadequate. This condition has the potential to reduce the level of consumer satisfaction and the business image in the eyes of customers. The aim of the research is to explore product quality at Family Cattering MSMEs in Bogor, identifying the main problems that arise in Family Cattering. The research uses qualitative methods, through direct observation of production and presentation procedures, as well as interviews with business owners. The data obtained was analyzed descriptively to describe actual conditions in the field. Research findings show that there are still problems with presentation indicators, including packaging that is easily damaged, lack of business identity in packaging design, and an unattractive buffet layout. The texture of the rice is too soft and the taste of the food is uneven is the main problem with the taste. Meanwhile, in innovative food (food innovation), Family Cattering already has quite a variety of menus, but innovation in developing new menus and serving is still limited. This research emphasizes that presentation by adding additional mats or containers made from mica, packaging so that it is not plain, changing water products to better known brands, varying batik motifs, making buffet tables more regular, taste adjustments in water dosage and cooking time. This research can be used as a guide for academics, practitioners, business people and other stakeholders.